Holes of hope and uncertainty – test wells as a site of potential, exploration and the verdict on Greenland’s oil development in the 1970s and 1990s - Priebe, Janina; Mårald, Erland; Vikström, Hanna (The Polar Journal, 2024)
This study examines the history of oil development in Greenland with a focus on test wells – the physical sites where and when the future of Arctic oil as an energy source was established and eventually abandoned. The processes surrounding the establishment of the first offshore test wells in the 1970s and the first onshore test well in the 1990s illustrate different contexts of oil development, as well as the similarities between the different phases. Looking at these periods through the lens of infrastructural delay, an umbrella concept that unites anthropological analyses of unfinished, delayed or unrealised infrastructure, this study shows how common themes of potential, exploration and verdict emerge that accompanied the establishment of physical test wells. Based on a thematic analysis of historical scientific and policy reports as well as Greenlandic media accounts, this study brings together a top-down and a local perspective on the construction of test wells in the 1970s and 1990s. This study advances research on the history of Arctic oil development by identifying the different phases of its delay that accompanied the creation of its physical infrastructure, each of which generated different social processes of hope and despair, and which also lay the foundation for future perspectives on the use of Greenland’s subsurface beyond oil. Validerad;2025;Nivå 1;2025-02-27 (u4); Fulltext license: CC BY Peripheral Visions: Global Agendas meet Nordic Energy Peripheries